Dealing with Female Brain-Drain in Rural Europe: Results from the CENTRAL EUROPE Project WOMEN. - (:unkn) unknown (My University, 2014)
Aus dem Inhalt: 1. Karin Wiest: Relevance and Intention of the CENTRAL EUROPE Project WOMEN Karin Wiest (S. 8 ff.); Rick Glöckner, Tim Leibert, Karin Wiest: 2. European Territories Affected by Selective Migration: Socio-Economic Structures and the Labour Market for Women in the Study Regions (S. 13 ff); 3. Tim Leibert: Selective Migration and Brain-Drain in Rural Regions: Patterns and Explanations (S. 25 ff.); 4. Tim Leibert: Demographic Trends and Developments: The Study Regions in a European Comparison (S. 36 ff.); 5. Rick Glöckner, Karin Wiest: Attempts to Explain the Female Brain-Drain: The View of Regional Experts (S. 53 ff.); 6. Matthias Schaarwächter, Anika Schmidt: Strategies against the Female Brain-Drain in Rural Europe: Lessons Learnt from the Awareness Raising Campaign, Demography Coaching and Networking Activities (S. 75 ff.); 7. Matthias Schaarwächter, Anika Schmidt, Karin Wiest: Transferability and Sustainability of the WOMEN Project Results - an Outlook (S. 91 ff.).
Keywords: Bevölkerungsentwicklung; Frau; Abwanderung; Ländlicher Raum; Bevölkerungswanderung; Geschlecht; Segregation; Arbeitsmarkt; Migration; Gender; Internationaler Vergleich